Clinical relevance of appraisals of persistent psychotic experiences in people with and without a need for care: an experimental study. (December 2017) - Peters, Emmanuelle; Ward, Thomas; Jackson, Mike; Woodruff, Peter; Morgan, Craig; McGuire, Philip; Garety, Philippa A
Summary: Background: Cognitive models of psychosis propose that appraisals (ie, the interpretation and meaning attributed to experiences) are central to the transition from anomalous experiences to psychotic symptoms. In the Unusual Experiences Enquiry (UNIQUE) study, we investigated the role of appraisals by comparing individuals with persistent psychotic experiences without a need for care with patients and people without psychotic experiences. Method: Eligible participants were patients with diagnosed psychotic disorders (clinical group) and adults in the general population with persistent psychotic experiences (non-clinical group) and without psychotic experiences (controls). The appraisals of psychotic experiences among people in the non-clinical and clinical groups were assessed by an in-depth interview, and appraisals of anomalous experiences induced by three experimental tasks were compared between all groups. Findings: We recruited 259 participants, 84 in the clinical group, 92 in the non-clinical group, and 83 controls. The clinical group was more likely than the non-clinical group to display paranoid, personalising interpretations of their psychotic experiences (p<0·008; p values are Sidak adjusted to account for multiple testing) and less likely to have normalising (p<0·008) and supernatural (p=0·039) explanations. The clinical group also appraised their psychotic experiences as being more negative, dangerous, and abnormal and less controllable than the non-clinical group (all p<0·005), but groups did not differ for attributions of general externality (p=0·44). For experimentally induced anomalous experiences, the clinical group endorsed more threatening appraisals on all tasks than the non-clinical group (p<0·003), who did not differ from the control group (p=0·07–0·6). The pattern was similar for ratings of salience, distress, personal relevance, global threat, and incorporation of the induced experiences into participants' own psychotic experiences. Interpretation: We provide robust evidence that the way psychotic experiences are appraised differs between individuals with and without a need for care, supporting cognitive models of psychosis. Specifically, the absence of paranoid and threatening appraisals might protect against persistent psychotic experiences becoming clinically relevant. Funding: UK Medical Research Council.